The Effect of Risk Accumulation on Childhood Stunting: A Matched Case-Control Study in China - Tang, Xiao; Zhao, Yanxiang; Liu, Qigui; Hu, Dongmei; Li, Guorong; Sun, Jin; Song, Guirong (Frontiers in Pediatrics, 2022)
Background: Childhood stunting is still a public health issue in developing countries. However, the traditional risk factors in underdeveloped areas are not suitable for developed areas. Moreover, childhood stunting is influenced by several aspects, including genetic factors, perinatal conditions, maternal conditions and feeding practices, but researchers have not yet clearly determined which aspect of risk accumulation exerts the strongest effect on stunting. A matched case–control study was performed to assess the effect of different aspects of risk accumulation on childhood stunting. Methods: In total, 173 and 173 nonstunted children aged less than seven years were matched in our study from June 2015 to August 2015. The children’s heights and weights were measured, and a self-administered questionnaire was used to collect information from the children and their parents. The risk factors were assigned to the following five aspects: genetic factors, family socioeconomic status, perinatal conditions, maternal conditions and feeding practices. The risk accumulation (cumulative risk score) in each aspect was defined as the total number of risk factors that occurred in a certain aspect. A conditional logistic regression model was used to assess the effect of risk accumulation in different aspects on stunting, and a decision-tree model was used to predict the children’s stunting based on the cumulative risk scores. Results: Risk accumulation in perinatal conditions, genetic factors, maternal conditions and feeding practices was significant in the conditional logistic regression model (P<0.05). Perinatal conditions showed the strongest association with stunting in both the regression analysis and the decision-tree model. The risk of stunting increased by 1.199 times if the cumulative risk score of perinatal conditions increased by one, and the probability of stunting was 75.8% if the cumulative risk score of perinatal conditions was ≥1. Conclusions: Risk accumulation in perinatal conditions, genetic factors, maternal conditions and feeding practices substantially increased the probability of childhood stunting. Perinatal conditions were the main aspect associated with stunting. Prevention and intervention measures should be adopted to avoid risk accumulation in stunting.